Potential role of social impact bond and socially responsible investment sukuk as financial tools that can help address issues of poverty and socio-economic insecurity - Syed Azman, Syed Marwan Mujahid; Engku Ali, Engku Rabiah Adawiah (IIUM Press, 2016)
The purpose of this paper is to highlight the potential of Social Impact Bond (SIB) and Socially Responsible Investment (SRI) sukuk as financial models that can be used to help alleviate the social problem of poverty and also potentially provide economic security for the society. From the review of literature, this paper takes case studies of SIB programmes and SRI sukuk, and relates them as programmes that can be used to address the issue of poverty and economic insecurity. The paper finds that there is a growing global interest in innovative financial tools such as SIB and SRI sukuk. Furthermore, the paper explicates that SIB and SRI sukuk models embody the spirit of social responsibility, which is one of the major essence that is currently missing in the Islamic finance industry practice. This paper is conceptual and exploratory in nature. Therefore, further empirical research can be done to provide better understanding and knowledge. Findings from this paper can be used as a reference to understand the concepts and mechanisms involved in SIB and SRI sukuk models. This paper contributes to the awareness of the emerging global interest in SIB and SRI. In addition, it highlights SIB and SRI sukuks' potential contribution towards Islamic finance. Although SIB and SRI sukuk is gaining interest worldwide, it has not caught much attention of researchers and practitioners involved with Islamic finance. Therefore, this paper offers insight towards SIB and SRI sukuk, which is relatively unknown to academics and Islamic finance industry practitioners.